Anti-Tumor Effect of Apatinib and Relevant Mechanisms in Liposarcoma - Cui, Lixuan; Yan, Liang; Guan, Xiaoya; Dong, Bin; Zhao, Min; Lv, Ang; Liu, Daoning; Wang, Zhen; Liu, Faqiang; Wu, Jianhui; Tian, Xiuyun; Hao, Chunyi (Frontiers in Oncology, 2021)
Background: Primary retroperitoneal liposarcomas (RLPSs) are rare heterogeneous tumors for which there are few effective therapies. Certain anti-angiogenic tyrosine kinase inhibitors have demonstrated efficacy against various solid tumors. The aims of this study were to investigate the effect of Apatinib against retroperitoneal liposarcoma cells and its underlying mechanism and to explore the anti-tumor efficacy of a combination of Apatinib and Epirubicin. Methods: CD34 immunohistochemical staining to measure microvessel density（MVD）in 89 retroperitoneal liposarcoma tissues. We used CCK-8 cell proliferation, clone formation, Transwell migration, and invasion assays and flow cytometry to evaluate the effects of Apatinib alone and the combination of Apatinib and Epirubicin on liposarcoma cells. High-throughput RNA sequencing and western-blotting was used to identify key differentially expressed genes (DEGs) in SW872 cell line after application of Apatinib. Murine patient-derived tumor xenograft（PDX）was established to assess the efficacy and safety of Apatinib monotherapy and the combination of Apatinib and Epirubicin in RLPS. Results: The microvessel density (MVD) varied widely among retroperitoneal liposarcoma tissues. Compared with the low-MVD group, the high-MVD group had poorer overall survival. Apatinib inhibited the liposarcoma cell proliferation, invasion and migration, increased the proportion of apoptosis, and induced G1 phase arrest. In addition, the combination of Apatinib and Epirubicin enhanced the foregoing inhibitory effects. High-throughput RNA sequencing showed that Apatinib downregulated the expression of TYMS and RRM2. Western blotting verified that Apatinib downregulated the TYMS/STAT3/PD-L1 pathway and inhibited liposarcoma proliferation by suppressing the RRM2/PI3K/AKT/mTOR pathway. In the murine PDX model of retroperitoneal liposarcoma, Apatinib and its combination with Epirubicin significantly inhibited microvessel formation and repressed tumor growth safely and effectively. Conclusions: Apatinib and its combination with Epirubicin showed strong efficacy against liposarcoma both in vitro and in vivo. Apatinib might inhibit liposarcoma cell proliferation through the RRM2/PI3K/AKT/mTOR signaling pathway and downregulate PD-L1 via the TYMS/STAT3 signaling pathway.